Organic silicon heat-conducting gasket and preparation method thereof
By employing sheet-like boron nitride orientation and surface modification in silicone thermal pads, combined with nanomaterials and fiber-reinforced fillers, a silicone thermal pad with high thermal conductivity and high resilience is prepared, solving the problem of balancing thermal conductivity and resilience in existing technologies, and making it suitable for the heat dissipation needs of electronic devices.
Patent Information
- Application Number
- CN202511334979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2025-11-21
AI Technical Summary
Existing silicone thermal pads cannot maintain high thermal conductivity while also possessing high resilience and electrical insulation, thus failing to meet the comprehensive needs of electronic devices in diverse application scenarios.
Using sheet-like boron nitride as a thermally conductive filler, a vertically oriented thermally conductive network is formed by aligning the silicone thermal pads in the thickness direction. After surface modification treatment, combined with nanomaterials and fibrous reinforcing fillers, and using addition-curing silicone rubber as the matrix, the silicone thermal pads are prepared by multiple coating and curing processes.
It achieves high thermal conductivity and high resilience in the vertical direction of the gasket with a relatively low thermally conductive filler content, ensuring the flexibility and processability of the material, making it suitable for applications requiring electrical insulation.
Smart Images

Figure CN120988489A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of silicone heat-conducting pads, in particular to a silicone heat-conducting pad and a preparation method thereof. BACKGROUND
[0002] In the field of heat dissipation of electronic devices such as smart phones, CPUs, GPUs, power modules and new energy automobile batteries, efficient thermal management is crucial to ensure device performance, stability and service life. Silicone heat-conducting pads are widely used as interface heat-conducting materials filled between heat-generating bodies and heat sinks due to their excellent electrical insulation, wide temperature resistance (-50℃ to 200℃), good flexibility and convenient construction.
[0003] With the rapid development of electronic devices towards miniaturization and high power density, the heat generated per unit area has increased sharply, which puts higher requirements on the performance of heat-conducting materials. An ideal heat-conducting pad not only needs to have a high thermal conductivity to quickly conduct heat, but also must have excellent high resilience (low permanent compression deformation) to ensure that it can maintain close contact with the interface under long-term vibration, impact conditions and different assembly pressures, maintain stable low thermal resistance and avoid the decline of heat dissipation efficiency due to stress relaxation.
[0004] Currently, to improve the heat-conducting performance of silicone heat-conducting pads, the conventional technical means mainly include increasing the filling amount of heat-conducting fillers, selecting high-thermal-conductivity fillers and optimizing the silicone matrix formula. Specifically, increasing the addition amount of heat-conducting fillers (such as alumina, magnesium oxide, etc.) can effectively improve the thermal conductivity of the material; selecting high-thermal-conductivity fillers such as boron nitride and aluminum nitride can further improve the heat-conducting performance; and adjusting the composition and crosslinking system of the silicone matrix can improve the flexibility and resilience of the material to some extent. However, the above methods often fail to balance high thermal conductivity and high resilience: increasing the amount of fillers tends to harden the material and reduce its resilience; relying solely on matrix optimization has limited effect on improving the heat-conducting performance.
[0005] It is worth noting that in recent years, methods of using graphene or carbon fibers as heat-conducting fillers and preparing heat-conducting pads through orientation arrangement process have appeared. Such materials show good performance in terms of heat-conducting and resilience performance. However, their inherent electrical conductivity leads to poor insulation performance of the final product, which cannot be applied to occasions requiring electrical insulation, severely limiting their application range.
[0006] Although the prior art has made some progress in improving the thermal conductivity of silicone thermal pad, there are still significant deficiencies: first, the use of high filler content and traditional thermal fillers often sacrifices material resilience and flexibility; second, the application of non-insulating fillers such as graphene and carbon fiber can improve thermal conductivity and resilience, but cannot meet the insulation requirements; third, the existing technical solutions are not adaptable to diversified application scenarios, and it is difficult to meet the comprehensive needs of high thermal conductivity, high resilience and high insulation.
[0007] Therefore, the present application provides a silicone thermal pad and a preparation method thereof. SUMMARY
[0008] The present application aims to provide a silicone thermal pad and a preparation method thereof, which can achieve extremely high thermal conductivity in the vertical direction with relatively low thermal filler content. At the same time, when compressed, the sheet-shaped boron nitride is more likely to deflect elastically rather than be crushed, thereby significantly improving the compression resilience of the pad.
[0009] The object of the present application is achieved by adopting the following technical solutions:
[0010] On the one hand, the present application provides a silicone thermal pad, which comprises the following components by weight:
[0011] Silicone matrix: 10 to 50 parts;
[0012] Thermal filler: 20 to 80 parts;
[0013] Nanomaterial: 1 to 10 parts;
[0014] Fibrous reinforcing filler: 1 to 10 parts;
[0015] Among them, the thermal filler includes sheet-shaped boron nitride, which is oriented and arranged in the thickness direction of the silicone thermal pad, forming a vertically oriented thermal network.
[0016] The beneficial effects of the above scheme are that the silicone heat-conducting gasket of the present application is set by components to ensure that the amount of heat-conducting filler is sufficient to form a high-efficiency heat-conducting network (realize high heat conduction), and at the same time there is enough silicone matrix to wrap the heat-conducting filler, which ensures the flexibility and processability of the material (realize high resilience). The nanofiller fills the gap between the large-particle-size BN, and the fibrous reinforcing filler plays a reinforcing and connecting role, and the three work together to maximize the heat-conducting filler content while avoiding the problem of too hard and poor resilience of the material. In addition, traditional randomly distributed heat-conducting fillers need a very high filling amount to form a heat-conducting path, and are isotropic. The vertical network structure of the sheet-shaped boron nitride enables heat to be efficiently transferred in the thickness direction of the gasket along the plane direction of the sheet-shaped boron nitride (i.e. the direction with the highest thermal conductivity of the sheet-shaped boron nitride), realizing anisotropic heat conduction. It can be seen that the present application can achieve extremely high thermal conductivity in the vertical direction with relatively low heat-conducting filler content. At the same time, when compressed, the sheet-shaped boron nitride is more likely to elastically deflect rather than be crushed, thereby significantly improving the compression resilience of the gasket.
[0017] Further, the sheet-shaped boron nitride is subjected to surface modification treatment, and the surface modification treatment includes acid washing and hydroxylation and grafting treatment with a silane coupling agent.
[0018] Further, the average particle size of the sheet-shaped boron nitride is 5 to 150 μm.
[0019] Further, the silane coupling agent is selected from one or a combination of two of γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane.
[0020] Further, the nanomaterial is selected from one or a combination of two of nanometer aluminum oxide and nanometer zinc oxide.
[0021] Further, the fibrous reinforcing filler is selected from one or a combination of two or more of aluminum oxide fiber, zinc oxide fiber, and aluminum nitride fiber.
[0022] Further, the silicone matrix is addition-cured silicone rubber.
[0023] Further, the silicone matrix includes the following components by weight:
[0024] Vinyl silicone oil: 20 to 100 parts;
[0025] Hydrogen-containing silicone oil: 1 to 10 parts;
[0026] Catalyst: 0.1 to 2 parts;
[0027] Inhibitor: 0.1 to 1 part.
[0028] Further, the vinyl silicone oil is an end-vinyl silicone oil, and the viscosity is 50 mPa·s to 50000 mPa·s;
[0029] Further, the hydrogen content of the hydrogen-containing silicone oil is 0.05wt% to 1.5wt%;
[0030] Further, the catalyst is a platinum-gold catalyst;
[0031] Further, the inhibitor is selected from one or a combination of 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, 1.3.5.7-tetraethynyl-1.3.5.7-tetramethylcyclotetrasiloxane.
[0032] In another aspect, the present application provides a preparation method of a silicone heat-conducting gasket, comprising the following steps:
[0033] Step a: mixing and stirring the silicone matrix, the heat-conducting filler, the nanomaterial, and the fibrous reinforcing filler uniformly to obtain a mixed slurry; wherein the heat-conducting filler comprises surface-modified flaky boron nitride;
[0034] Step b: performing multiple times of blade coating molding and curing the mixed slurry on a substrate to obtain a silicone heat-conducting blank with the flaky boron nitride oriented in the thickness direction;
[0035] Step c: cutting the silicone heat-conducting blank along a direction perpendicular to the blade coating plane to obtain a silicone heat-conducting gasket, wherein the silicone heat-conducting gasket has a vertically oriented heat-conducting network.
[0036] The above-mentioned scheme has the beneficial effect that under the action of shear force, the flaky boron nitride will be laid flat (i.e. parallel to the substrate plane) along the blade coating direction in the thin layer blade coating (≤0.3mm) of the preparation method of the present application. Through multiple times of blade coating molding and curing, the flaky boron nitride is vertically oriented, i.e. from the cutting surface, the flaky boron nitride is arranged in the thickness direction (Z direction). Cutting along a direction perpendicular to the blade coating plane (i.e. parallel to the orientation direction of the flaky boron nitride) makes the cross section of each small gasket the orientation plane of the flaky boron nitride, thereby exposing the vertically heat-conducting path in the thickness direction of the gasket.
[0037] Further, in step a: the stirring speed when stirring uniformly is 50 rpm, the stirring time is 1h, and the vacuum degree is -0.09MPa;
[0038] In step b: the curing temperature when molding and curing is 140℃ to 160℃, and the curing time is 5min to 15min.
[0039] Further, in step b: the thickness of a single time of blade coating the mixed slurry on the substrate is less than or equal to 0.3mm, and heating and curing are performed after each time of blade coating to make the flaky boron nitride of each layer lay flat and form
[0040] Compared with the prior art, the beneficial effects of the present application at least include:
[0041] The silicone heat-conducting gasket of the present application is set by components to ensure that the amount of heat-conducting filler is sufficient to form a high-efficiency heat-conducting network (realize high heat conduction), while there is enough silicone matrix to wrap the heat-conducting filler to ensure the flexibility and processability of the material (realize high resilience). The fibrous reinforcing filler fills the gap between the large-particle-size BN and plays a role in reinforcement and connection, and the three work together to maximize the content of heat-conducting filler while avoiding the problem of excessive hardness and poor resilience of the material. In addition, traditional randomly distributed heat-conducting fillers need a very high filling amount to form a heat-conducting path and are isotropic. The vertical network structure of the sheet-shaped boron nitride in the present application enables heat to be efficiently transferred in the thickness direction of the gasket along the plane direction of the sheet-shaped boron nitride (i.e. the direction with the highest thermal conductivity of the sheet-shaped boron nitride), realizing anisotropic heat conduction. It can be seen that the present application can achieve extremely high thermal conductivity in the vertical direction with relatively low heat-conducting filler content. At the same time, when compressed, the sheet-shaped boron nitride is more likely to elastically deflect rather than be crushed, thereby significantly improving the compression resilience of the gasket.
[0042] The thin layer of the preparation method of the present application is scraped to form a coating (≤0.3 mm), and under the action of shear force, the sheet-shaped boron nitride will lay flat in the scraping direction (i.e. parallel to the plane of the substrate). Through multiple scraping and curing, the sheet-shaped boron nitride is vertically oriented, i.e. from the cutting surface, the sheet-shaped boron nitride is arranged in the thickness direction (Z direction). Cutting along the direction perpendicular to the scraping surface (i.e. parallel to the orientation direction of the sheet-shaped boron nitride) makes the cross section of each small gasket the orientation surface of the sheet-shaped boron nitride, thereby exposing the vertical heat-conducting path in the thickness direction of the gasket. BRIEF DESCRIPTION OF DRAWINGS
[0043] Figure 1 is a flowchart schematic diagram of the preparation method of the silicone heat-conducting gasket of the embodiment of the present application. DETAILED DESCRIPTION
[0044] Example embodiments will now be described more fully with reference to the accompanying drawings. Example embodiments, however, can be implemented in many different forms and should not be construed as limited to the implementations set forth herein; rather, these implementations are provided so that this disclosure will be thorough and complete, and will fully convey the inventive concept of example embodiments to those skilled in the art. Like reference numerals refer to like elements throughout the drawings, and thus a repetitive description of like elements will be omitted.
[0045] The words expressing position and direction described in the present application are explained by taking the drawings as an example, but changes can also be made as needed, and the changes made are included in the protection scope of the present application.
[0046] In order to improve the thermal conductivity of the silicone thermal pad and significantly improve the compression resilience, the application discloses a silicone thermal pad and a preparation method thereof.
[0047] The components of the silicone thermal pad of the application include, by weight: 10-50 parts of a silicone matrix (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 40 or 50 parts); 20-80 parts of a thermal conductive filler (for example, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 35, 40, 50, 60, 70 or 80 parts); 1-10 parts of a nanomaterial (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 parts); and 1-10 parts (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 parts) of a fibrous reinforcing filler.
[0048] The thermal conductive filler of the application includes flaky boron nitride, which is arranged in an orientation in the thickness direction of the silicone thermal pad, forming a vertically oriented thermal conductive network.
[0049] In some embodiments, the flaky boron nitride is subjected to surface modification treatment, which includes acid washing and hydroxylation and grafting treatment with a silane coupling agent.
[0050] The unmodified flaky boron nitride has poor compatibility with the silicone matrix, and there are a large number of air gaps at the interface, resulting in extremely high thermal resistance. After surface modification, the silane coupling agent forms a molecular bridge-like coupling effect between the flaky boron nitride and the silicone matrix, greatly improving the interface affinity, reducing the interface defects, and enabling heat to be more efficiently transferred from the silicone matrix to the thermal conductive filler (i.e., the flaky boron nitride) and then from the thermal conductive filler, thereby improving the overall thermal conductivity of the composite material (e.g., the silicone thermal pad). In addition, the strengthened interface bonding means that when the material is subjected to stress (such as compression, stretching), the stress can be effectively transferred from the relatively flexible silicone matrix to the high-modulus flaky boron nitride, avoiding interface debonding as the starting point of damage. The mechanical strength, tear resistance and resilience durability of the silicone thermal pad are significantly improved.
[0051] In some embodiments, the average particle size of the flaky boron nitride is 5-150 μm (e.g., 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, 6 μm, 70 μm, 80 μm, 9 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm). The flaky boron nitride in this particle size range is easy to achieve oriented arrangement in the process. Too large particle size is difficult to disperse and orient, and affects the surface flatness and flexibility of the gasket; too small particle size has extremely high surface energy, easy to agglomerate, and destroys the heat conduction path.
[0052] In some embodiments, the silane coupling agent is selected from one or a combination of two of γ-(methacryloyloxy)propyltrimethoxysilane KH-570 and dodecyltrimethoxysilane. These two coupling agents ensure the reliability and optimality of the surface modification effect: γ-(methacryloyloxy)propyltrimethoxysilane KH-570 contains a vinyl group that can chemically bond with the silicone matrix; dodecyltrimethoxysilane has a long-chain alkyl group that can provide excellent organic compatibility and hydrophobicity.
[0053] The nanomaterial of the present application is selected from one or a combination of two of nano-aluminum oxide and nano-zinc oxide.
[0054] The fibrous reinforcing filler of the present application is selected from one or a combination of two or more of aluminum oxide fiber, zinc oxide fiber, and aluminum nitride fiber. The fibrous reinforcing filler has two functions: one is to lap between different flaky boron nitride, acting as a heat conduction bridge to enhance the connectivity of the heat conduction network; the other is like a steel bar, which can significantly improve the mechanical strength, modulus, and creep resistance of the material, so that the gasket can still maintain good resilience under long-term pressure and prevent continuous loss of thickness.
[0055] The silicone matrix of the present application is an addition-cured silicone rubber. Compared with condensation-cured, addition-cured has the advantages of no by-products, uniform curing, strong depth curing ability, low modulus, high transparency, no odor, etc. This makes the silicone heat-conducting gasket have fewer internal defects, more stable performance, better resilience, and is more suitable for electronic application scenarios with strict requirements on VOC (volatile organic compounds).
[0056] In use, the components of the silicone matrix, in parts by weight, include: 20 to 100 parts of a vinyl silicone oil (e.g., 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 35 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, or 100 parts); 1 to 10 parts of a hydrogen-containing silicone oil (e.g., 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts); 0.1 to 2 parts of a catalyst; 0.1 to 1 part of an inhibitor (e.g., 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1.0 part, 1.5 parts, or 2.0 parts). The ratio of the vinyl silicone oil to the hydrogen-containing silicone oil determines the crosslinking density, which in turn affects the modulus and resilience of the gasket.
[0057] In some embodiments, the vinyl silicone oil is an end-vinyl silicone oil, and has a viscosity of 50 mPa-s to 50,000 mPa-s (e.g., 50 mPa-s, 51 mPa-s, 52 mPa-s, 53 mPa-s, 54 mPa-s, 55 mPa-s, 56 mPa-s, 57 mPa-s, 58 mPa-s, 59 mPa-s, 60 mPa-s, 65 mPa-s, 70 mPa-s, 80 mPa-s, 90 mPa-s, 100 mPa-s, 200 mPa-s, 300 mPa-s, 400 mPa-s, 500 mPa-s, 600 mPa-s, 700 mPa-s, 800 mPa-s, 900 mPa-s, 1,000 mPa-s, 2,000 mPa-s, 3,000 mPa-s, 4,000 mPa-s, 5,000 mPa-s, 6,000 mPa-s, 7,000 mPa-s, 8,000 mPa-s, 9,000 mPa-s, 10,000 mPa-s, 20,000 mPa-s, 30,000 mPa-s, 40,000 mPa-s, or 50,000 mPa-s). A suitable viscosity facilitates the dispersibility of the filler and the leveling of the subsequent doctor-blade process: too low a viscosity cannot support the filler, which tends to settle; too high a viscosity makes processing difficult.
[0058] Further, the hydrogen content of the hydrogen-containing silicone oil is related to the crosslinking density, which is a key parameter for controlling the hardness and resilience of the final product. In some embodiments, the hydrogen content of the hydrogen-containing silicone oil is 0.05 wt% to 1.5 wt% (e.g., 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, 0.10 wt%, 0.20 wt%, 0.30 wt%, 0.40 wt%, 0.50 wt%, 0.60 wt%, 0.70 wt%, 0.80 wt%, 0.90 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, or 1.5 wt%).
[0059] In some embodiments, the catalyst is a platinum gold catalyst.
[0060] Further, the inhibitor can effectively control the reaction rate, prevent violent polymerization, and give the mixed slurry a good operating life, leaving sufficient time for the doctor blade process. In some embodiments, the inhibitor is selected from one or a combination of 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, 1.3.5.7-tetraethynyl-1.3.5.7-tetramethylcyclotetrasiloxane.
[0061] Reference Figure 1 The method for preparing the silicone heat-conducting gasket of the present application comprises steps a to c.
[0062] Step a: mix and stir the silicone matrix, the heat-conducting filler, the nanomaterial, and the fibrous reinforcing filler uniformly to obtain a mixed slurry. The heat-conducting filler comprises surface-modified sheet-like boron nitride.
[0063] In application, the weight ratio of the silicone matrix, the heat-conducting filler, the nanomaterial, and the fibrous reinforcing filler is (10 to 50):(20 to 80):(1 to 10):(1 to 10).
[0064] In actual application, in step a, the stirring speed when stirring uniformly is 50 rpm, the stirring time is 1 h, and the vacuum degree is -0.09 MPa, so as to ensure uniform dispersion of the heat-conducting filler and sufficient defoaming of the mixed slurry, avoiding air bubbles from becoming thermal resistance points and mechanical defect points.
[0065] In some embodiments, (1) the hydroxylated treatment of the flaky boron nitride: a mixed solution is prepared by mixing hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 1:3; the mixed solution is mixed with the flaky boron nitride, stirred at a speed of 300 rpm / min for 2 h, and then anhydrous ethanol is added, after which the flaky boron nitride is filtered out, and the flaky boron nitride is washed with deionized water until it is neutral, and then dried by baking, to obtain flaky boron nitride whose surface is hydroxylated. (2) The silane coupling agent treatment of the hydroxylated flaky boron nitride: the hydroxylated flaky boron nitride and the silane coupling agent are added to a high-speed blender, the reaction system is heated to 80°C, the stirring speed is 1000 rpm / min, and the stirring reaction time is 2 h.
[0066] In some embodiments, the weight ratio of the mixed solution, the flaky boron nitride, the anhydrous ethanol, and the silane coupling agent is (100-80):(100-80):(100-80):1.
[0067] Step b: the mixed slurry is formed and cured on the substrate by multiple times of blade coating, to obtain a silicone heat-conducting body in which the flaky boron nitride is oriented in the thickness direction.
[0068] In application, in step b: the thickness of the mixed slurry coated on the substrate in a single time is less than or equal to 0.3 mm, and heating and curing are performed after each time of coating, so that the flaky boron nitride in each layer is laid out. In this thickness window, the flaky boron nitride can be effectively oriented by shear force, and the orientation of the flaky boron nitride inside can be ensured without disturbance such as convection during curing due to excessive thickness. Preferably, the thickness of the mixed slurry coated on the substrate in a single time is 0.05 mm to 0.3 mm (for example, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.10 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.2 mm, or 0.3 mm). More preferably, the thickness of the mixed slurry coated on the substrate in a single time is 0.2 mm.
[0069] In actual application, in step b: the curing temperature during the formation and curing is 140°C to 160°C (for example, 140°C, 145°C, 150°C, 155°C, or 160°C), and the curing time is 5 min to 15 min (for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min). This temperature window can ensure that the addition reaction proceeds efficiently and is fully cured, and can prevent the inhibitor from failing or the silicone matrix from degrading due to excessively high temperature. This time window is sufficient to ensure that each layer is fully cured to support the blade coating of the next layer.
[0070] In practical applications, the thickness of the silicone heat-conducting blank is 10 mm to 500 mm, for example, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 25 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm, 200 mm, 300 mm, 400 mm, or 500 mm.
[0071] Step c: cutting the silicone heat-conducting blank in a direction perpendicular to the doctoring plane to obtain a silicone heat-conducting gasket, the silicone heat-conducting gasket having a vertically oriented heat-conducting network.
[0072] In applications, cutting along a direction perpendicular to the doctoring plane (i.e., parallel to the orientation direction of the sheet-shaped boron nitride) makes the cross section of each small gasket the orientation plane of the sheet-shaped boron nitride, thereby exposing the vertical heat-conducting path in the thickness direction of the gasket.
[0073] In order to make the purpose, technical scheme and advantages of the present application more clear, the present application is further described in detail by setting specific examples and comparative examples. It should be understood that the specific examples and comparative examples described herein are only used to explain the present application and do not limit the present application.
[0074] The raw materials in the examples and comparative examples of the present application: a vinyl silicone oil with a viscosity of 500 cs, purchased from Zhejiang Runhe Organic Silicon New Material Co., Ltd.; a vinyl silicone oil with a viscosity of 1000 cs, purchased from Zhejiang Runhe Organic Silicon New Material Co., Ltd.; a hydrogen-containing silicone oil with a hydrogen content of 0.10 wt%, purchased from Zhejiang Runhe Organic Silicon New Material Co., Ltd.; a hydrogen-containing silicone oil with a hydrogen content of 0.15 wt%, purchased from Zhejiang Runhe Organic Silicon New Material Co., Ltd.; a platinum catalyst, purchased from Zhongshan Dixin Chemical Co., Ltd.; an ethynylcyclohexanol inhibitor, purchased from Zhongshan Dixin Chemical Co., Ltd.; anhydrous ethanol, purchased from Ningbo Xiyide Chemical Co., Ltd.; dodecyltrimethoxysilane, purchased from Hangzhou Jessica Chemical Co., Ltd.; gamma-(methacryloyloxy)propyltrimethoxysilane KH-570, purchased from Hangzhou Jessica Chemical Co., Ltd.; hydrogen peroxide with a concentration of 5 wt%; concentrated sulfuric acid with a concentration of 98 wt%.
[0075] The test standard for the thermal conductivity of the silicone heat-conducting gasket of the present application is ISO 22007-2; the test standard for the resilience rate is ASTM D2632; and the test standard for the electric strength is EN 60243-1.
[0076] Example 1
[0077] This example introduces a preparation method of a silicone heat-conducting gasket, and the materials in this example are shown in Table 1.
[0078] The preparation method of the embodiment comprises steps SS1 to SS6.
[0079] Step SS1: a mixed solution prepared by mixing hydrogen peroxide and concentrated sulfuric acid at a volume ratio of 1:3, the mixed solution is mixed with boron nitride, and stirred at a speed of 300 rpm / min for 2 h; anhydrous ethanol is added, flaky boron nitride is filtered out, and the flaky boron nitride is washed with deionized water until it is neutral, and then dried by baking, so that the surface of the flaky boron nitride is hydroxylated.
[0080] Step SS2: The hydroxylated flaky boron nitride is added to a high-speed blender, and then a silane coupling agent is continuously added. Then the temperature of the reaction system is heated to 80°C, and the stirring speed is 1000 rpm / min, and the reaction is stirred for 2 h to obtain surface-modified flaky boron nitride.
[0081] Step SS3: The vinyl silicone oil, hydrogen-containing silicone oil, catalyst and inhibitor are uniformly mixed to obtain a silicone matrix. The weight ratio of the vinyl silicone oil, hydrogen-containing silicone oil, catalyst and inhibitor is 1000:10:1:1.
[0082] Step SS4: The silicone matrix, surface-modified flaky boron nitride, nanomaterial and fibrous reinforcing filler are added to a planetary mixer and mixed and stirred to obtain a mixed slurry. The stirring speed is 50 rpm, the stirring time is 1 h, and the vacuum degree is -0.09 MPa.
[0083] Step SS5: The mixed slurry is scraped on the squeegee with a scraper, the thickness of each layer of scraping is controlled to be 0.2 mm, and after baking in a 150°C oven for 10 min, the next layer is continuously scraped, and baking and curing are performed again. The silicone heat-conducting blank is obtained by continuously scraping in turn until the required thickness of 50 mm is reached.
[0084] Step SS6: The silicone heat-conducting blank is vertically cut by an ultrasonic cutting machine to obtain a silicone heat-conducting gasket.
[0085] The silicone heat-conducting gasket of the embodiment has a thermal conductivity of 18 W / (m·K), a resilience rate of 95%, and an electric strength of 15 KV / mm.
[0086] Table 1 Material components of Example 1
[0087]
[0088]
[0089] Example 2
[0090] The embodiment introduces a preparation method of a silicone heat-conducting gasket.
[0091] The difference between the embodiment and Example 1 is
[0092] (1) The selection and amount of the materials are shown in Table 2.
[0093] (2) The weight ratio of the vinyl silicone oil, hydrogen-containing silicone oil, catalyst and inhibitor is 450:10:1:1.
[0094] The thickness of each layer of the doctor blade coating is controlled to be 0.15 mm.
[0095] The thickness of the silicone heat-conducting blank is 50 mm.
[0096] The thermal conductivity of the silicone heat-conducting gasket of the present example is 15 W / (m·K), the resilience rate is 92%, and the electric strength is 16 KV / mm.
[0097] Table 2 Material components of Example 2
[0098]
[0099]
[0100] Comparative Example 1
[0101] The present comparative example introduces a preparation method of a silicone heat-conducting gasket, and the selection and amount of the materials of the present comparative example are the same as those of Example 1.
[0102] The difference between the present comparative example and Example 1 is that the step SS5.
[0103] Step SS5 of Comparative Example 1: The mixed slurry is once-pressed to form a sheet, and is baked in a 150℃ oven for 10 min to obtain a silicone heat-conducting blank.
[0104] The thermal conductivity of the silicone heat-conducting gasket of the present comparative example is 3.5 W / (m·K), the resilience rate is 35%, and the electric strength is 11 KV / mm.
[0105] Comparative Example 2
[0106] The present comparative example introduces a preparation method of a silicone heat-conducting gasket, and the selection and amount of the materials of the present comparative example are the same as those of Example 2.
[0107] The difference between the present comparative example and Example 2 is that:
[0108] (1) The selection and amount of the materials are shown in Table 3.
[0109] (2) Step SS5: The mixed slurry is once-pressed to form a sheet. The viscosity of the mixed slurry of the present comparative example is too large, and cannot be once-pressed to form a sheet.
[0110] Table 3 Material components of Comparative Example 2
[0111]
[0112] In summary of the above embodiments, the present application selects flaky boron nitride as a heat-conducting filler, significantly improves the heat-conducting performance of the material in the thickness direction by constructing a vertically oriented heat-conducting path, enhances the compatibility of the flaky boron nitride with the organic silicone matrix by surface modification treatment, optimizes the interface structure, and further improves the overall heat-conducting efficiency, introduces nanomaterials and fibrous reinforcing fillers to effectively fill the gaps in the heat-conducting network and enhance the connectivity of the path, thereby synergistically improving the thermal conductivity and resilience of the material, uses addition-cured silicone as the matrix to achieve excellent flexibility, resilience and stability, ensuring reliable performance of the material in various working environments, and optimizes the component ratio and preparation process to achieve the organic unity of high thermal conductivity and high resilience, meeting the increasing performance requirements of electronic equipment for heat dissipation materials.
[0113] The silicone heat-conducting gasket of the present application has wide application potential in the fields of electronic equipment heat dissipation, new energy vehicle battery thermal management, LED lighting, etc. With the continuous development of electronic equipment towards high performance and high integration, the present application can effectively improve the comprehensive performance of the heat-conducting gasket and meet the high-efficiency heat dissipation requirements. At the same time, in the field of new energy vehicles, the silicone heat-conducting gasket of the present application helps to improve the heat dissipation efficiency of the power battery, prolong the service life, and promote the healthy development of the industry. In addition, in the field of LED lighting, the application of the silicone heat-conducting gasket of the present application can improve the heat dissipation performance of the lamp, improve the light efficiency and reliability, and promote the popularization of energy-saving lighting.
[0114] Although the embodiments of the present application have been shown and described above, it should be understood that the above embodiments are exemplary and should not be construed as limiting the present application. Those skilled in the art can make changes, modifications, replacements and variations to the above embodiments without departing from the principles and purposes of the present application within the scope of the present application. All these changes should be within the protection scope of the claims of the present application.
Claims
1. A silicone thermally conductive pad, characterized in that, Based on parts by weight, it includes the following components: Organosilicon matrix: 10 to 50 parts; Thermally conductive filler: 20 to 80 parts; Nanomaterials: 1 to 10 parts; Fiber-reinforced filler: 1 to 10 parts; The thermally conductive filler includes sheet-like boron nitride, which is oriented in the thickness direction of the silicone thermally conductive pad to form a vertically oriented thermally conductive network.
2. The silicone thermal pad according to claim 1, characterized in that, The plate-like boron nitride undergoes surface modification treatment, which includes acid washing and hydroxylation, as well as grafting treatment using a silane coupling agent.
3. The silicone thermal pad according to claim 2, characterized in that, The average particle size of the plate-shaped boron nitride is 5 μm to 150 μm; And / or, the silane coupling agent is selected from one or a combination of two of γ-(methacryloyloxy)propyltrimethoxysilane and dodecyltrimethoxysilane.
4. The silicone thermal pad according to claim 1, characterized in that, The nanomaterial is selected from one or a combination of two of nano-alumina and nano-zinc oxide; And / or, the fibrous reinforcing filler is selected from one or more combinations of alumina fibers, zinc oxide fibers, and aluminum nitride fibers.
5. The silicone thermal pad according to claim 1, characterized in that, The organosilicon matrix is an addition-cured silicone rubber.
6. The silicone thermal pad according to claim 5, characterized in that, The organosilicon matrix comprises the following components in parts by weight: Vinyl silicone oil: 20 to 100 parts; Hydrogen-containing silicone oil: 1 to 10 parts; Catalyst: 0.1 to 2 parts; Inhibitor: 0.1 to 1 part.
7. The silicone thermal pad according to claim 6, characterized in that, The vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity of 50 mPa·s to 50000 mPa·s; And / or, the hydrogen content of the hydrogen-containing silicone oil is from 0.05 wt% to 1.5 wt%; And / or, the catalyst is a platinum catalyst; And / or, the inhibitor is selected from one or a combination of several of 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, and 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane.
8. A method for preparing an organosilicon thermal pad, characterized in that, Includes the following steps: Step a: Mix and stir the organosilicon matrix, thermally conductive filler, nanomaterials and fibrous reinforcing filler to obtain a mixed slurry; wherein, the thermally conductive filler includes surface-modified lamellar boron nitride; Step b: The mixed slurry is repeatedly coated and cured on the substrate to obtain a sheet-like boron nitride oriented organosilicon thermally conductive preform in the thickness direction; Step c: Cut the silicone thermally conductive preform along a direction perpendicular to the coating plane to obtain a silicone thermally conductive pad, wherein the silicone thermally conductive pad has a vertically oriented thermally conductive network.
9. The preparation method according to claim 8, characterized in that, In step a: the stirring speed when mixing is uniform is 50 rpm, the stirring time is 1 h, and the vacuum degree is -0.09 MPa; In step b: the curing temperature during molding and curing is 140℃ to 160℃, and the curing time is 5 min to 15 min.
10. The preparation method according to claim 8, characterized in that, In step b: the thickness of the mixed slurry applied to the substrate in a single coat is less than or equal to 0.3 mm, and each coat is heated and cured to make each layer of sheet boron nitride flat and formed.
Citation Information
Cited By
Preparation method of heat-conducting gasket on intelligent communication terminal, heat-conducting gasket and application of heat-conducting gasket
CN121699229A
A filler-oriented heat-conductive gasket and a method for manufacturing the same
CN122356815A